Editorials without Editors: a Possible Reality? - Belkis González Aguiar; Alain Francisco Morejón Giraldoni; Pablo Manuel Guerra Martí (Revista Finlay)
It is unfair, even illogical the job of editors do not recieve the diserved acknowledgement; for the many working hours and concern on the work; for the comittment with the information analyzed; for the required knowledge to honor others research; for the abilities and competences acquired during professional development. In addition, at present editors have in their hands the gratests texts of philosophers, scientists and researchers, requires for those professionals that in a silent way permeate them of their wisdom and intuition.